Homosexuality between Men in Britain since the Eighteenth Century - Cocks, Harry (History compass, 2007)
Historians have tended to agree that homosexuality is defined more by culture than nature. However, they disagree over the question of how exactly culture and history shape sexual practices and identity. A few years ago, historians sought to find the origins of modern homosexuality, and tended to treat homosexuality as one thing. It was assumed that modern homosexuality meant an association with effeminacy, and that the effeminate homosexual was a creation of the eighteenth century. Now, however, historians see homosexuality as a diverse phenomenon, encompassing a wide range of behaviour and identity, and have tried to dismantle the idea that it must have a unitary history. Historians have also become much more interested in the continuities between present and past behaviour. They have also given a new prominence to social factors, rather than sexual ones, in the formation of sexuality.